FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PUBLIK DALAM ADMINISTRASI PEMERINTAHAN DI INDONESIA - Rahyunir Rauf (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
Government in general is an organization given legitimacy by the people as the holder of sovereignty to carry out the duties of government in the country, as well as equipped with state-fittings .. The government is an organization that has; The governing authorities of a political unit, the ruling power of a political society, the apparatus is functioning government agencies and the exercise of power, the power to make laws dealing with disputes and discuss the decision of the administration with a monopoly on the legitimate power. Essential functions of government, namely; service (service), empowerment (empowerment) and development (development). Public service is a public bureaucracy production received citizen users. Related awareness of government officials towards the delivery of public services, in fact, not all government officials aware of the importance of service. In fact, sometimes the expression "if it can be made more difficult, why is it easy?", Which is always circulating among government officials in the public service, it shows that they are generally not aware of their position as public servants and also the philosophy of the service itself. Other facts also show that the educational curriculum and training for government officials in various types and levels, less gave the charge on the general aspects of service management. Problems of the poor quality of public services in Indonesia, namely; Still low competence of the State Civil Apparatus (ASN) in the implementation of public services in Indonesia. Still lack of professional ASN, ASN still low morale. is still a lack of motivation in the development of the ASN ASN. Research results indicate that Factor Employee Competency, Professionalism Employees, Employee Morale and Motivation Employee Giving effect on the level of the quality of public services in Indonesia.